Specific low-frequency electromagnetic fields induce expression of active KDM6B associated with functional changes in U937 cells. (2nd April 2020) - Pinton, Giulia; Ferraro, Angelo; Balma, Massimo; Moro, Laura
ABSTRACT: In this study, we investigated the effects of specific low-frequency electromagnetic field sequences on U937 cells, an in vitro model of human monocyte/macrophage differentiation. U937 cells were exposed to electromagnetic stimulation by means of the SynthéXer system using two similar sequences, XR-BC31 and XR-BC31/F. Each sequence was a time series of 29 wave segments, equal to a total duration of 77 min. Here, we report that exposure (4 d, once a day) of U937 cells to the XR-BC31 setting, but not to the XR-BC31/F, resulted in increased expression of the histone demethylase KDM6B along with a global reduction in histone H3 lysine 27 tri-methylation (H3K27me3). Furthermore, exposure to the XR-BC31 sequence induced differentiation of U937 cells towards a macrophage-like phenotype displaying a KDM6B dependent increase in expression and secretion of the anti-inflammatory interleukins (ILs), IL-10 and IL-4. Importantly, all the observed changes were highly dependent on the nature of the sequence. Our results open a new way of interpretation for the effects of low-frequency electromagnetic fields observed in vivo . Indeed, it is conceivable that a specific low-frequency electromagnetic fields treatment may cause the reprogramming of H3K27me3 and cell differentiation.